2022
DOI: 10.3390/toxins14030182
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Mechanism and Biological Detoxification of Fumonisins

Abstract: Food safety is related to the national economy and people’s livelihood. Fumonisins are widely found in animal feed, feed raw materials, and human food. This can not only cause economic losses in animal husbandry but can also have carcinogenicity or teratogenicity and can be left in animal meat, eggs, and milk which may enter the human body and pose a serious threat to human health. Although there are many strategies to prevent fumonisins from entering the food chain, the traditional physical and chemical metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 97 publications
(114 reference statements)
0
17
1
4
Order By: Relevance
“…Aflatoxin M1 (AFM1) is the monohydroxylated metabolite of AFB1 which is similarly toxic and carcinogenic and is secreted in the milk of cows fed on AFB1-contaminated diets. , Analysis of AFM1 in milk is therefore of importance in checking for food safety and AFB1 exposure, using several methods including chromatography. This carry-over of AFB1 to milk as AFM1 ranges from less than 1% to 6.2% and may be affected by, among other factors, the level of milk production, breed, and presence of other mycotoxins. Fumonisins on the other hand are not excreted in milk but have a synergistic effect when they co-occur with AF in pigs , and humans in the induction of liver disease . Hence, we hypothesize that the co-occurrence of AF and FUM may increase the uptake of AF and its subsequent carry-over to milk.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Aflatoxin M1 (AFM1) is the monohydroxylated metabolite of AFB1 which is similarly toxic and carcinogenic and is secreted in the milk of cows fed on AFB1-contaminated diets. , Analysis of AFM1 in milk is therefore of importance in checking for food safety and AFB1 exposure, using several methods including chromatography. This carry-over of AFB1 to milk as AFM1 ranges from less than 1% to 6.2% and may be affected by, among other factors, the level of milk production, breed, and presence of other mycotoxins. Fumonisins on the other hand are not excreted in milk but have a synergistic effect when they co-occur with AF in pigs , and humans in the induction of liver disease . Hence, we hypothesize that the co-occurrence of AF and FUM may increase the uptake of AF and its subsequent carry-over to milk.…”
Section: Introductionmentioning
confidence: 98%
“…This carry-over of AFB1 to milk as AFM1 ranges from less than 1% to 6.2% and may be affected by, among other factors, the level of milk production, breed, and presence of other mycotoxins. 24−27 Fumonisins on the other hand are not excreted in milk but have a synergistic effect when they co-occur with AF in pigs 13,28 and humans in the induction of liver disease. 29 Hence, we hypothesize that the co-occurrence of AF and FUM may increase the uptake of AF and its subsequent carry-over to milk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our findings reported that the ET emission is dependent on the applied FB1 concentration in both mature tomato genotypes after 72 h which could contribute to higher lipid peroxidation and EL from WT leaves. High lipid peroxidation (expressed in terms of MDA) directly corresponds to enhanced oxidative stress producing more reactive lipid peroxide radicals and disrupting structural and functional properties of lipids under FB1 stress (Qu et al 2022). Likewise, more EL from FB1-treated leaves denotes cell death induced by an oxidative burst and is dependent on the applied concentration of FB1 (Otaiza-González et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The main aspect of fumonisin toxicity is the inhibition of ceramide synthesis and the disruption of sphingolipid metabolism, which can cause cell apoptosis [ 122 ]. This mechanism of action stems from the similarity between the chemical structure of fumonisins and the structure of sphingosine (the primary part of sphingolipids), which is why they are recognised, and bound, by ceramide synthase [ 123 ].…”
Section: Toxicologymentioning
confidence: 99%